La frontière entre le Mexique et le Guatemala : une frontière « poreuse » ? - Jean Clot (IdeAs)
The Mexico-Guatemala border is frequently referred to as a “porous border.” The phrase is found in various fields, such as politics, the media, academia, and international and nongovernmental institutions, which would tend to make “porosity” an inherent characteristic of that border. However, is “porosity” a neutral, descriptive term? Is it a mere analogy borrowed from the vocabulary of the natural sciences? This article will attempt to define the meaning of the term by paying close attention to its definitions and figurative uses in the context of the Mexican-Guatemalan borderland. It also aims at highlighting the symbolic scope of the notion, as well as its origin in order to achieve a better understanding of the issues at stake in the field of migration and international relations. Finally, it will draw a comparison with other border regions so as to stress the need for critical distance and to open new avenues for future exploration.